Lived experiences of women who transitioned from heterosexuality to lesbianism. - Cabaluna, Mary Joy S.; Duallo, Geoffrey S.; Salva, Christine Joy N. (Mary Joy S. Cabaluna, 2013)
Few researches have been conducted about women's lived experiences in transitioning to a new sexual orientation. This study was conducted to answer the need for these researches regarding a woman's shift of attraction to identifying one's own lesbian orientation. Attraction, as used in this study, is closely linked to sexual orientation; hence, it is believed that women undergo transformations in their sexual orientation. This qualitative study looks into the experiences of women who underwent a transition of sexual orientation from heterosexuality to lesbianism. Six women who identified themselves as lesbians were selected and interviewed to understand the experiences of women who underwent transitions in their sexual orientations, the contributors to the shift of another orientation, as well as emotional experiences associated with the shift. Results reflected four major themes: (1) orientation identification which encompasses the participant's experiences of lesbian attraction, confusion, curiosity, exploration, acceptance, control over one's orientation, and reflections; (2) factors of lesbian attraction, which describes the elements that influenced lesbian attraction; (3) positive and negative emotional experiences that tackle emotions of happiness or sadness in terms of the participant's orientation; and lastly, the theme that presents the (4) participants' perceived possible future with regard to their sexual orientation.